Building industrial digital twins : design, develop, and deploy digital twin solutions for real-world industries using Azure Digital Twin /: design, develop, and deploy digital twin solutions for real-world industries using Azure Digital Twin. (2021) - Nath, Shyam Varan; Van Schalkwyk, Pieter
No abstract available